Online Exhibitions during the COVID-19 Pandemic. Issue 1 (1st July 2020) - Hoffman, Sheila K.
Abstract : In the mid-1990s, when many museums were beginning to take their first hesitant steps toward building online personae, the worry still holding many back was that if a collection or experience were available online, in-person visitation would invariably decline (Anderson 1996 ; Cody 1997 ; Wallace 1995 ). In the 25 years since, that fear has largely been dispelled even as our technical ability to digitally capture and disseminate cultural collections has improved exponentially, even to the point that the online experience in some ways exceeds the in-person experience. Indeed, museums have moved far beyond the ability to show a few images of the major works in a collection, adding opportunities that mirror almost all the offerings of the in-person experience. But even this "Mona Lisa" effect has not driven in-person visitation down. Rather the opposite. Anyone who has elbowed through the crowds at many of the world's best-known museums can attest to that. Indeed, having been among this ubiquitous press of people, I could not help but think on such occasions that it would take an act of God to reduce the numbers and improve the quality of viewing.